1988
DOI: 10.3758/bf03213486
|View full text |Cite
|
Sign up to set email alerts
|

Memory access: The effects of fact-oriented versus problem-oriented acquisition

Abstract: This study examined the effects of similarity between the processing of acquisition and the processing of test materials on performance in a problem solving task. Previous work by Perfetto, Bransford, and Franks (1983) demonstrated that uninformed subjects' failure to utilize relevant acquisition information in a later problem solving task is the result of a failure to spontaneously access such information. The present study demonstrated that spontaneous access can be enhanced when both acquisition and test ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
52
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(55 citation statements)
references
References 17 publications
3
52
0
Order By: Relevance
“…In the work on analogous problems, the consensus is that remindings are affected both by structural similarities between the problems (i.e., those aspects that are relevant to the problems' solutions) and by superficial similarities between the problems (e.g., Holyoak & Koh, 1987;Ross, 1987). In a similar vein, the recent work on accessing nonanalogous information has shown that access will increase if subjects can be cued to encode (and focus on) the relevant aspects (Stein et al, 1986) or if subjects process the information in a way that is similar to the way they will need to process it at the time the riddle is presented (e.g., Adams et al, 1988;Lockhart et al, 1988). Gentner and Landers (1985) and Stein et al (1986) also showed that superficial similarities can affect access.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…In the work on analogous problems, the consensus is that remindings are affected both by structural similarities between the problems (i.e., those aspects that are relevant to the problems' solutions) and by superficial similarities between the problems (e.g., Holyoak & Koh, 1987;Ross, 1987). In a similar vein, the recent work on accessing nonanalogous information has shown that access will increase if subjects can be cued to encode (and focus on) the relevant aspects (Stein et al, 1986) or if subjects process the information in a way that is similar to the way they will need to process it at the time the riddle is presented (e.g., Adams et al, 1988;Lockhart et al, 1988). Gentner and Landers (1985) and Stein et al (1986) also showed that superficial similarities can affect access.…”
Section: Discussionmentioning
confidence: 92%
“…This last finding provides further support for earlier studies (e.g., Perfetto et al, 1983;Weisberg et al, 1978) that indicated the difficultysubjectshad with spontaneously accessingrelevant information. If we are to learn what conditions promote access (e.g., Adams et al, 1988;Lockhart et al, 1988), it is also important to understand the conditions under which spontaneous access does not occur.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Against a tradition that has mainly shown poor transfer of solution methods when hints to use prior analogues have not been provided, a few studies point to the importance of transferappropriate processing (e.g., Adams et al, 1988; Gick & McGarry, 1992;Lockhart, Lamon, & Gick, 1988;Stein, Way, Benningfield, & Hedgecough, 1986). Consider a set of experiments by Needham and Begg (1991): Some of their subjects tried to solve training analogues before they were taught their solutions, while the others studied the analogues and tried to remember them before the solutions were taught.…”
mentioning
confidence: 99%